Managing Investment Climate Reform : Case Study of Uganda Telecommunications - Byaruhanga, Charles (Washington, DC: World Bank, 2012)
The reform of the telecommunications sector in Uganda demonstrates success both in outcome and in terms of the management of the process. This study provides a description of the reforms and the resulting benefits. It identifies the role of different interest groups and institutions, how consensus for reform was built, and how reform design and implementation was undertaken.